2016
DOI: 10.1111/nph.14223
|View full text |Cite
|
Sign up to set email alerts
|

Singlet oxygen initiates a plastid signal controlling photosynthetic gene expression

Abstract: Summary Retrograde signals from the plastid regulate photosynthesis‐associated nuclear genes and are essential to successful chloroplast biogenesis. One model is that a positive haem‐related signal promotes photosynthetic gene expression in a pathway that is abolished by the herbicide norflurazon. Far‐red light (FR) pretreatment and transfer to white light also results in plastid damage and loss of photosynthetic gene expression. Here, we investigated whether norflurazon and FR pretreatment affect the same ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 72 publications
1
51
0
Order By: Relevance
“…The question of whether a weaker nuclear gene expression indicates the action of a negative signal or the missing action of a positive signal has been debated in the past (Pfannschmidt, 2010;Terry and Smith, 2013;Hills et al, 2015). A recent study (Page et al, 2017a(Page et al, , 2017b and our data presented here indicate that the action of both positive and negative signals needs to be considered in current models.…”
Section: Retrograde Control Of Nuclear Gene Expression By Biogenic Plmentioning
confidence: 74%
See 1 more Smart Citation
“…The question of whether a weaker nuclear gene expression indicates the action of a negative signal or the missing action of a positive signal has been debated in the past (Pfannschmidt, 2010;Terry and Smith, 2013;Hills et al, 2015). A recent study (Page et al, 2017a(Page et al, , 2017b and our data presented here indicate that the action of both positive and negative signals needs to be considered in current models.…”
Section: Retrograde Control Of Nuclear Gene Expression By Biogenic Plmentioning
confidence: 74%
“…Proteins proposed to act as plastid signals include envelope-tethered eukaryotic transcription factors TFIIB-like and PTM, both being released from the outer plastid membrane by targeted proteolysis (Lagrange et al, 2003;Sun et al, 2011) and a plastid localized Whirly1 protein that is released from plastids upon stress (Isemer et al, 2012). A very recent study, however, puts this particular function of PTM in retrograde signaling into question (Page et al, 2017a(Page et al, , 2017b. Most of these retrograde signaling molecules are discussed as stress signals operating from fully developed chloroplasts.…”
mentioning
confidence: 99%
“…Although the volatile compound ethylene has been shown to induce shade avoidance characteristics (Pierik et al ., ,b), our literature search failed to find a particular study that shows volatile compounds such as ethylene emanating from neighbouring weeds can increase 1 O 2 production in crop plants. In contrast, our ‘in planta’ demonstration of rapid 1 O 2 production in soyabean leaves in response to neighbouring weeds corresponds well with a recent study, where continuous FR pre‐treatment of Arabidopsis seedlings before transfer to continuous white light resulted in rapid 1 O 2 production in rosette leaves (Page et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Retrograde signaling from the developing chloroplast (plastid) to the nucleus, which is termed biogenic signaling (Pogson et al, 2008), can be revealed using either the bleaching herbicide Norflurazon (NF), an inhibitor of carotenoid synthesis, or the plastid translation inhibitor, lincomycin (Lin) to damage the plastid. Under these conditions there is a strong downregulation of hundreds of nuclear genes (Koussevitzky et al, 2007;Aluru et al, 2009;Page et al, 2017). Despite decades of research, the biogenic retrograde signaling pathway is still very poorly understood.…”
mentioning
confidence: 99%